2015
DOI: 10.1016/j.rboe.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty with mobile tibial weight-bearing: clinical evaluation after a minimum of five years of postoperative follow-up

Abstract: ObjectiveTo evaluate the medium and long term results from total knee arthroplasty with rotating tibial weight-bearing.MethodsBetween January 2000 and July 2007, 162 patients underwent total knee arthroplasty with mobile tibial weight-bearing. Among these, 96 were evaluated in a previous study with a mean follow-up of 4 years. In the present study, the same group was invited back for reassessment and the results were analyzed. Sixty-nine patients responded to this call (79 knees), and they were evaluated in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…We know that the implant is just one of the factors that lead to a successful procedure [7][8] . There are several other factors that hinder the analysis of the results of arthroplasties in our country, such as: the heterogeneous characteristics of the services that perform arthroplasties; the lack of documentation of results; the low adherence of patients to long-term follow-ups (especially in cases with good results); cultural, structural, and socioeconomic issues that limits the access to medical services 1,14 . Our study showed, as well as the few previous case series using Brazilian implants [5][6] that the Brazilian implant has results comparable to the imported.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the implant is just one of the factors that lead to a successful procedure [7][8] . There are several other factors that hinder the analysis of the results of arthroplasties in our country, such as: the heterogeneous characteristics of the services that perform arthroplasties; the lack of documentation of results; the low adherence of patients to long-term follow-ups (especially in cases with good results); cultural, structural, and socioeconomic issues that limits the access to medical services 1,14 . Our study showed, as well as the few previous case series using Brazilian implants [5][6] that the Brazilian implant has results comparable to the imported.…”
Section: Discussionmentioning
confidence: 99%